Art therapy in the correction of the psychoemotional state of patients who have suffered stroke at the stage of medical rehabilitation - V. I. Ruzov; K. A. Sayfutdinov; O. N. Vylegzhanina; D. V. Kolchin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Considering the high incidence of stroke in the post-pandemic period COVID-19, it is necessary to carry out a set of rehabilitation measures for these patients aimed at their integration into society. One of the most common consequences of a stroke is cognitive deficit and psycho-emotional lability. Among the psychotherapeutic methods for correcting these disorders, art therapy has become widespread.Purpose of the study: to evaluate the effectiveness of the art therapy method in correcting the psycho-emotional state of patients who suffered stroke at the stage of medical rehabilitation.Object and methods. The study involved 110 patients who had suffered stroke, randomized into 2 groups using art therapy and humanistic psychotherapy. The assessment was carried out using the MMSE and HADS test.Results. The results obtained indicate the advantage of art therapy in correcting the psycho-emotional state of patients; however, this type of psychotherapy does not affect the dynamics of cognitive functions in patients with stroke.Conclusions. Art therapy is one of the most optimal methods of psychological correction, the psycho-emotional state of patients with stroke and does not affect cognitive functions. In the rehabilitation of patients with stroke, it is necessary to combine various methods of psychotherapy.